Peer support as part of scaling-up integrated care in patients with type 2 diabetes and arterial hypertension at the primary healthcare level - Virtič, Tina (Zdravstveno varstvo, 2023)
Introduction: Type 2 diabetes (T2D) and arterial hypertension (AH) are among the greatest challenges facing health systems worldwide and require comprehensive patient-centred care. The key to successful management in chronic patients is self-management support, which was found to be only weakly implemented in Slovenia. The aim of the study is to develop an evidence-based model of peer support for people with T2D and AH at the primary healthcare level in Slovenia, which could represent a potential solution for upgrading integrated care for these patients.Methods: A prospective interventional, mixed-methods pilot study will begin by recruiting approximately 40 eligible people with T2D and AH through purposive sampling. The participants will receive structured training, led by a specialist nurse, to become trained peer supporters. Each will voluntarily share their knowledge and experience at monthly group meetings with up to 10 people with T2D and AH over a three-month period in the local community. Data will be collected through interviews and focus groups and questionnaires about socio-demographic and clinical data, knowledge about T2D and AH, participants’ quality of life, level of empowerment and acceptability of the intervention.Expected results: The study will provide an evidence-based model for integrating peer support into the local community. It is expected that the intervention will prove feasible and acceptable with educational, psychosocial and behavioural benefits.Conclusion: Peer support through empowerment of people with T2D and AH, family members and other informal caregivers in the local community could scale-up the integrated care continuum and contribute to sustainability of the healthcare system.
Keywords: arterial hypertension; arterijska hipertenzija; diabetes type 2; laična podpora; peer support; sladkorna bolezen tipa 2